2013
DOI: 10.1016/j.bbr.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the therapeutic effects of bone marrow mononuclear cells and microglia for permanent cerebral ischemia

Abstract: In this study we transplanted bone marrow mononuclear cells (BM-MNCs) or microglia into rats that had undergone permanent cerebral ischemia and observed the distribution or morphology of transplanted cells in vivo. In addition, we also compared the effects of BM-MNCs and microglia on infarct volume, brain water content, and functional outcome after permanent cerebral ischemia. BM-MNCs and microglia were obtained from femur and brain, respectively, of newborn rats. Adult rats were injected with vehicle or 3 mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 40 publications
3
30
0
1
Order By: Relevance
“…The pro-angiogenic potentials of BM-MNCs and BMSCs have been demonstrated not only in skin flap survival model but also in the other ischemic diseases [7,8,[13][14][15][16][17]. However, which is the optimal cell source for clinical application is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-angiogenic potentials of BM-MNCs and BMSCs have been demonstrated not only in skin flap survival model but also in the other ischemic diseases [7,8,[13][14][15][16][17]. However, which is the optimal cell source for clinical application is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…On days 1, 3, 7, 14, 21, and 28 after TBI, neurologic deficit was evaluated with the modified neurologic severity score (mNSS), which measures motor, sensory, reflex, and balance deficits (Zhang et al 2009; Jiang et al 2013). The mNSS test is graded on a scale of 0 (normal) to 18 (maximal deficit).…”
Section: Methodsmentioning
confidence: 99%
“…C57BL/6 was anaesthetized with pentobarbital (150 mg/kg), and Pagination not final (cite DOI) / Pagination provisoire (citer le DOI) BMCs were isolated from the tibias and femurs Jiang et al 2013). The medullar cavities of the bones were exposed and flushed with DMEM (Dulbecco's Modified Eagle's Medium, Sigma-Aldrich, St. Louis, Missouri, USA), pH 7.2 .…”
Section: Bmcs Transplantationmentioning
confidence: 99%
“…Studies have shown that endothelial progenitor cells can repair and renovate some specific arterial physiological conditions. For example, progenitor cells stabilize atherosclerotic plaque in pathological conditions (Xu 2008), and studies have shown that the infusion of BMCs is neuroprotective after permanent brain ischemia (Jiang et al 2013). Moreover, other studies have shown that endothelial progenitor cells contribute to the formation of atherosclerotic lesions (Fadini et al 2007).…”
Section: Introductionmentioning
confidence: 98%